ENGARUH PEMBERIAN KULIT KOPI TERFERMENTASI DAN LEGUMINOSA UNTUK PERTUMBUHAN KAMBING PERANAKAN ETAWAH - Londra, I Made (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2013)
Waste coffee planthas the potential to be used as abooster feed for livestock. Coffee fruit waste composition physicallyquite largeat around 48% on coffee pulp. Research was conducted to examine the effect on the growth of Etawah CrossbredGoat (PE) after the treatment of fermented coffee waste as the substitution for leguminous (gamal and kaliandra). Twelve5-6 months old male PE goats were involved with 20 kg early weight average. Three groups of feeding treatment wereconsidered: Treatment P1 = 100% leguminous (gamal and kaliandra in ratio 1:1); Treatment P2 = 70% leguminous(gamal and kaliandra in ratio 1:1) + 30% fermented coffee Pulp; Treatment P3 = 40% leguminous (gamal and kaliandrain ratio 1:1) + 60% fermented coffee Pulp. Result of research indicated that the average increase of daily body weightof PE goat in the Treatment P1 (88.93 grams/goat/day) and P2 (100.00 grams/goat/day) was not obviously different (P> 0.05), but both were obviously different (P < 0.05) from P3 (71.79 grams/goat/day). Treatment P3 showed the lowestlevel of the consumption of DM, OM and the lowest level of gross energy, and had obvious difference (P < 0.05) fromP1 and P2. Meanwhile, P1 and P2 were not obviously different (P > 0.05). From these results, it was concluded that thetreatment of fermented coffee Pulp by 30 % and of leguminous (gamal and kaliandra) by 70 % (at P2) were giving thebest growth for PE goat. Indeed, P2 also displayed the most efficient food conversion.